Evaluation Of Combined Metformin-Lovastatin Therapy In The Treatment Of Diabetic Type 2 Patients With Dyslipidemia In Hospital Pulau Pinang - Ghaith, Nada Faisal Zaki (2010)
Diabetes type 2 is characterized by the presence of insulin resistance which frequently co-exists with multiple cardiovascular risk factors. Dyslipidemia is a well-recognized and modifiable risk factor that should be identified and treated aggressively to prevent the onset and prognosis of cardiovascular disease. This study aimed to assess the clinical outcomes behind the usage of metformin and lovastatin in the treatment of diabetes type 2 patients with dyslipidemia. Furthermore, an evaluation of difference in therapeutic response was done according to race and gender. A retrospective observational study was performed at the outpatient clinic of Hospital Pulau Pinang, Malaysia. Demographic, medication profile, and laboratory tests information were collected. Data were analyzed by using Statistical Package of Social Sciences (SPSS) program version 15. From 873 medical records, only 501 patients met the inclusion criteria of this study. Females constituted 55.9%, while 44.1% were males. Racial distribution showed that Chinese were 41.7%, Malay 34.3% and Indians 24%. Significantly, Chinese showed the highest percentage (97.5%) of controlled HDL levels. Unlike males, females demonstrated the highest mean TC and HDL values (5.40 ± 1.09 mmol/l and 1.32 ± 0.29 mmol/l respectively) significantly.